Análise da entrecasca do cajueiro (Anacardium occidentale) e da ameixa do mato (Ximenia americana) no coto umbilical de caprinos e ovinos como antisséptico natural - Faraj, Khaled Salim Dantas Aby (2015)
By theincreasing of pathogenic microorganisms resistance´s to drugs due to the indiscriminate use of antibiotics, there is the concern to seek alternative therapies. The diversity of medicinal plants known in the Caatinga is high and getting in the community suggests a strong correlation between the using and traditional knowledge of these plants. During breastfeeding, the umbilical stump becomes gateway to pathogens that can cause infection and subsequent death of the animals. The objective is to characterize the technological and social aspects of decoction use as an antiseptic of the inner bark of cashew (Anacardium occidentale) and bush plum (Ximeniaamericana) in the umbilical stump of sheep and goats in settlements of Mossoró / RN with producers of the “Associação de Criadores de Caprinos do Oeste Potiguar e Região de Mossoró –ASCCOM”. Statistical analysis (in vitro) was used a completely randomized arrangement, considering as treatments the concentrations of 100%, 50%, 25%, 12,5% and iodine and chlorhexidine as a positive control with three replicates in the analysis of inhibition of bacterial growth halo, with its analysis of variance (ANOVA) followed by the application of the Tukey test at 5% probability. In the in vivo analysis, the application of decoctions happened once daily for 6 days and were collected swabs of navels and sent to the Veterinary Microbiology Laboratory of UFERSA, this was used Kruskal-Wallis test at 5% probability in comparison of treatments with iodine glycerin, decoction of the bark of A. occidentaleand X. americana., to observe the growth of bacterial colonies forming units. For the statistical analysis of data collected in the questionnaires it was used descriptive statistics. The results obtained for the presence of microorganisms such as Actinomycesspp., Acinetobacterspp., Aeromonasspp., Bacillus coagulans, Corynebacteriumsp., Citrobactersp., Escherichia coli, Enterobactersp., Pasteurella sp., Stomatococcusspp. Staphylococcusspp. and Xanthomonas maltophilia. The decoctions of A. occidentaleand X.americanapresented a great antiseptic action in vitroand in vivo. Most respondents had the age over of forty years old and had knowledge about the use of medicinal plants, had incomplete primary education and form of income was livestock. It was observed that Xamericana.is the most widely used plant. The main therapeutic indication is for wounds, the most used part of the inner bark and tea was, however, used orally or topically. A. occidentaleand knew X. Americanas herbal and had onfalopatia inthe cattle.The minority conductedtreatment with medicinal plants, although they believe in the use of medicinal plants efficiency. Most producers affirmed that the knowledge of the use of medicinal plants was passed on through family were traditional knowledge and conservation by maintaining the nature reserve. The inner bark of the cashew action prevents onfaloflebite. We can conclude that the plants A. occidentaleand X.americanaare an alternative as antiseptics, as well as the use of traditional knowledge about plants are a reality in the rural settlements of Mossoró / RN